2022
DOI: 10.2174/1570159x20666220114153308
|View full text |Cite
|
Sign up to set email alerts
|

The Role of High Mobility Group Box 1 (HMGB1) in Neurodegeneration: A Systematic Review

Abstract: Background: High mobility group box 1 (HMGB1) protein is a damage-associated molecular pattern (DAMP) molecule that plays an important role in the repair and regeneration of tissue injury. It also acts as a pro-inflammatory cytokine through the activation of toll-like receptor 4 (TLR4) and receptor for advanced glycation end products (RAGE), to elicit the neuroinflammatory response. HMGB1 may aggravate several cellular responses which may lead to pathological inflammation and cellular death. Thus, there have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…The loading solvent, composed of water/acetonitrile (99.7:0.3 v/v) with 0.2% formic acid, was used at a rate of 10 µL/min for 3 min. During the analysis, the 10-port valve was initially set at the loading position (1-2) with the loading solvent, and after 3 min, it switched to the analysis position (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). At this point, the trapping column was connected to the analytical column, and the loaded samples were back ushed into the analytical column.…”
Section: Nano-lc-prm/hrmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loading solvent, composed of water/acetonitrile (99.7:0.3 v/v) with 0.2% formic acid, was used at a rate of 10 µL/min for 3 min. During the analysis, the 10-port valve was initially set at the loading position (1-2) with the loading solvent, and after 3 min, it switched to the analysis position (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). At this point, the trapping column was connected to the analytical column, and the loaded samples were back ushed into the analytical column.…”
Section: Nano-lc-prm/hrmsmentioning
confidence: 99%
“…It has been reported that HMGB1 can be secreted into the circulation in numerous diseases including neurodegeneration 10 , Alzheimer disease 11 , lung disease 12 , and a wide range of cancers including gastric cancer 13 , colorectal cancer 13,14 , hepatocellular carcinoma 13 , pancreatic cancer 13,15 , nasopharyngeal carcinoma 13 , head and neck squamous-cell carcinoma 13,16 , esophageal cancer 13 , malignant pleural mesothelioma 13 , bladder cancer 13 , prostate cancer 13,17 , ovarian cancer 17 , lung cancer 18 , and cervical carcinoma 13 . Fewer studies have examined the secretion of HMGB2 19 , although it was recently discovered that nuclear HMGB2 makes an important contribution to the differentiation and survival of functional memory cells and stem-like progenitor exhausted T cells 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral small vessel disease refers to a series of clinical, imaging and pathological syndromes caused by various etiologies affecting small arteries and their distal branches, micro-arteries, capillaries, micro-venules and small veins in the brain. CMBs are a type of brain parenchymal damage caused by injury to the micro-vessels of the brain, whose main pathological changes are the deposition of iron-containing hemoglobin at the lesion as well as lipid hyalinosis of the micro-arteries and amyloid deposition in the vessel wall ( Ikram et al, 2022 ). CMBs have been found to be widely present in patients with cognitive impairment due to cerebrovascular disease and neurodegenerative disorders, and there is a correlation between the number of CMBs and their location in the brain and cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…High Mobility Group Protein B1 is an inflammatory factor and damage signaling molecule that affects the structural and functional changes of the blood-brain barrier (BBB) and has a role in regulating innate immunity and inducing the release of other inflammatory factors ( Xue et al, 2021 ). In the presence of central nervous system damage caused by inflammation, neurodegenerative lesions, and vascular damage, HMGB1 is rapidly released and inhibits synaptic plasticity by modulating the inflammatory response, exacerbating the pathological damage to damaged tissues ( Ikram et al, 2022 ), ultimately leading to learning memory decline and cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%